Individuals’ Desire for Social Needs Sharing Among Healthcare Providers: Findings from the 2022 Health Information National Trends Survey - Olvera, Ramona G.; Swoboda, Christine M.; Joseph, Joshua J.; Bose-Brill, Seuli; McAlearney, Ann Scheck; Walker, Daniel M. (Journal of general internal medicine : JGIM, 2025)
Increasingly, health systems are collecting and using social needs data, yet there is limited information about individuals' preferences for how social needs information is shared among providers for treatment purposes. To explore the connection between experiencing social needs and concerns about healthcare providers sharing social needs information. A nationally representative, cross-sectional study of 6252 US community-dwelling adults (≥ 18 years of age) who responded to the Health Information National Trends Survey (HINTS 6) (response rate 28.1%) from March to November 2022. Core measures include experiencing social needs in the past year (food, transportation, housing issues), and comfort with providers sharing social needs information with each other for treatment purposes. Other key independent variables included patient-centered communication, discrimination, trust, and quality of care. Odds of reporting experiencing a social need varied by age, race, education, and income, yet those 75 years or older (compared to ages 18-34) had higher odds of reporting feeling comfortable with providers sharing information about social needs. Those who reported having experienced discrimination in healthcare had lower odds of reporting comfort with providers sharing information about food (adjusted odds ratio [aOR], 0.63; 95% confidence interval [CI], 0.41-0.98) and transportation (aOR, 0.64; 95%CI, 0.44-0.94) needs. Those who trusted the healthcare system had higher odds of being comfortable with providers sharing information about unmet needs for food (aOR, 1.33; 95%CI, 1.07-1.65). Also, those who report better patient-centered communication and quality of care had higher odds of being comfortable with providers sharing information on unmet social needs. Individuals' preferences regarding social needs information sharing for treatment purposes, as well as experience of discrimination, trust in healthcare, quality of care, and patient-provider communication, should be considered in health system efforts to capture social needs information.